2018 International Conference on Information Management and Technology (ICIMTech) 2018
DOI: 10.1109/icimtech.2018.8528178
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of MOOC (Massive Open Online Course) Platforms of edX and Coursera (Study Case: Student of Programming Courses)

Abstract: The recent development of e-learning platform has provided the learning environment with exciting experiences to teach a various and massive learners population using MOOC (Massive Open Online Courses) platforms such as edX, Coursera, etc. A large user uses these platforms to enhance their competency and improve their skills. Numerous platform of MOOC has been implemented in higher education institution, and the public debate about MOOC is growing; is the platform relevant to be formal education or not. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Herrera-urgiles and Peralta-bravo [42] support MOOCs with gamification elements to improve the students' performance in Object-Oriented programming courses. Oktavia [43] found significant results in examining the effectiveness of edX and Coursera MOOCs in programming learning and suggest researchers to conduct more studies specially in higher education sector. Lepp et al [44] found that MOOCs are effective way in programming learning and they introduced a troubleshooters for programming practices that are provided via MOOCs and realized that 90% of the participants believe that troubleshooters are helpful and 80% were happy to utilize them.…”
Section: Mooc Is An Effective Educational Mean For Pllmentioning
confidence: 97%
“…Herrera-urgiles and Peralta-bravo [42] support MOOCs with gamification elements to improve the students' performance in Object-Oriented programming courses. Oktavia [43] found significant results in examining the effectiveness of edX and Coursera MOOCs in programming learning and suggest researchers to conduct more studies specially in higher education sector. Lepp et al [44] found that MOOCs are effective way in programming learning and they introduced a troubleshooters for programming practices that are provided via MOOCs and realized that 90% of the participants believe that troubleshooters are helpful and 80% were happy to utilize them.…”
Section: Mooc Is An Effective Educational Mean For Pllmentioning
confidence: 97%
“…Glory et al (2019) evaluated the edX platform following the same criteria adopted by Hanifa et al (2019) and reported that the "add a post" and "add a response" buttons on edX discussion forums could be more self-evident if they were repositioned on the interface. Research that compares MOOC platforms has also focused on usability (c.f., Tsironis et al, 2016) and user satisfaction with respect to how various platform features support learning activities (Oktavia et al, 2018). Such usability and user studies do not shed light on the intersection of platform design and learning.…”
Section: Literature Reviewmentioning
confidence: 98%
“…MOOC (Massive Open Online Courses) Platforms: Such as Coursera, edX, and Khan Academy, offering online courses from various educational institutions and subjects [57].…”
Section: Digital Learning Environments and Platformsmentioning
confidence: 99%